Inhibition of Extracellular Calcium Influx Results in Enhanced IL-12 Production in LPS-Treated Murine Macrophages by Downregulation of the CaMKKβ-AMPK-SIRT1 Signaling Pathway - Xin Liu; Ning Wang; Yuanfeng Zhu; Yongjun Yang; Xiaoli Chen; Shijun Fan; Qian Chen; Hong Zhou; Jiang Zheng (Hindawi Limited, 2016)
Activated macrophages are the primary sources of IL-12, a key cytokine bridging innate and adaptive immunity. However, macrophages produce low amounts of IL-12 upon stimulation and the underlying regulatory mechanism remains unclear. In this study, we found a new calcium-dependent mechanism that controlled IL-12 production in LPS-treated murine macrophages. First, LPS was demonstrated to induce extracellular calcium entry in murine peritoneal macrophages and inhibition of calcium influx resulted in marked enhancement in IL-12 production. Then, withdrawal of extracellular calcium was found to suppress CaMKKβ and AMPK activation triggered by LPS while chemical inhibition or genetic knockdown of these two kinases augmented LPS induced IL-12 production. AMPK activation increased the NAD+/NADH ratio and activated Sirtuin 1 (SIRT1), a NAD+-dependent deacetylating enzyme and negative regulator of inflammation. Chemical inhibitor or siRNA of SIRT1 enhanced IL-12 release while its agonist suppressed IL-12 production. Finally, it was found that SIRT1 selectively affected the transcriptional activity of NF-κB which thereby inhibited IL-12 production. Overall, our study demonstrates a new role of transmembrane calcium mobilization in immunity modulation such that inhibition of calcium influx leads to impaired activation of CaMKKβ-AMPK-SIRT1 signaling pathway which lifts restriction on NF-κB activation and results in enhanced IL-12 production.